INTENTION TO USE M-WALLET APPLICATION: AN ADJUSTED MEASUREMENT OF FACILITATING CONDITIONS - Hernando, Hendrick; Prabowo, Suryo Hadi Wira; Hastuti, Farida Tri (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: M-wallets have become the most prominent financial technology in Indonesia. Thus, discerning the behavioral intention of using m-wallet apps and the related determinants is essential. This study proposes an extended indicator for facilitating conditions to fill the identified gap in previous studies. The influence of facilitating conditions on usage intention is also examined. Methods: This study employed PLS-SEM to validate our proposed indicator and research hypothesis. 122 m-wallet users in Madiun participated as the research respondents. Data from the respondents was analyzed through reflective and structural assessments. Results: The findings identified that the QR code policy was valid and reliable as an indicator for facilitating conditions. Through the structural model assessment, the impact of facilitating conditions on usage intention was found to be significant. Conclusion and suggestion: As a novel contribution, this study has provided the QR code policy as an extended indicator. In this situation, the government plays a consequential role in increasing m-wallet penetration. Moreover, m-wallet providers are suggested to take into consideration facilitating conditions, including user guidance and smartphone compatibility.